Universal Karma - Fisher, Gareth (Journal of global buddhism, 2023)
Drawing on recent ethnographic research at a temple-based Buddhist charitable foundation in mainland China, this study joins recent scholarship that questions an understanding of karma as a solely individual soteriological enterprise. It shows how both volunteers and paid staff at the charitable foundation, many of whom were practicing Buddhists, focused on helping both people and other sentient beings as soteriological goals in their own right apart from a consideration of individual karmic benefit. Inspired by environmental awareness, this soteriological orientation saw the karmic fate of all beings as inextricably bound together, an orientation we can refer to as universal karma.